Uncovering Challenges in Learning Mathematics: Student Voices from Gurukul Schools - Marasini, Manoj (Annual Oxford Journal, 2025)
This qualitative study explores the challenges faced by students in Gurukul schools of western Nepal in learning mathematics from their own perspectives. Despite mathematics being a foundational and essential subject for academic and career development, students encounter significant difficulties due to limited time for practice, the perceived low relevance of mathematics to their future careers, and the dominance of traditional, teacher-centered pedagogical methods. Participants highlighted the burden of numerous subjects and ritual duties in Gurukul schools that constrain time allocation for mathematics, contributing to anxiety and poor performance. Additionally, students reported a disconnect between mathematics learning and their life goals, leading to low motivation and engagement. The persistence of conventional teaching practices, characterized by rote learning and a lack of interactive materials, further hinders conceptual understanding and cognitive development. These findings underscore the need for time management strategies, contextualized teaching approaches, and pedagogy reform to improve mathematics learning and student outcomes in Gurukul schools. This study benefits educators, policymakers, and stakeholders by revealing students’ voices and recommending holistic solutions encompassing pedagogy, parental, and societal support.